Analyzing The Formulation of Business Strategy of Pelita Kita Trading Company - Susriyanti Susriyanti; Fitri Yeni; Riche Fermayani; Erwin H Harahap (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
Pelita Kita is a trading company that sells woods, windows frame, doors, panels and various types of processed woods. Using environmental analysis, the present study seeks to examine the formulation of business strategy as an effort to create a competitive advantage. Data were collected through interviews and questionnaires and then analyzed using the following matrices: IFE, EFE, CPM, TOWS, IE, and SPACE. The results of analysis revealed that the studied company may employ some alternative strategies such as market penetration and market development to compete. It is also concluded that market penetration is more preferable because it has a greater total value of attraction compared to other strategies.